A Systematic Review: The Effectiveness of Triple Drug versus Dual Drug Approach Against Lymphatic Filariasis - Devina Hanalily Maharani Ferguszon; Putri Cahya Purwaningrum; Raihanah labibah; Prawesty Diah Utami (Publication Department, Universitas Warmadewa, 2025)
Background: Lymphatic Filariasis (LF) is a neglected tropical disease caused by filarial nematode parasites (Wuchereria bancrofti, Brugia malayi, and B. timori), which is transmitted via mosquitoes in the form of microfilariae (Mf). The transmission cycle for each species is the same parasites or worms transmitted through the bite of all types of mosquitoes. The most severe clinical manifestations of LF are lymphedema and elephantiasis. The treatment of filariasis receives mass drug administration with a single dose of the triple-drug oral regimen. Therefore, the World Health Organization (WHO) reported that the triple-drug oral regimen was an LF treatment.Methods: The research is in the form of systematic review research using the PRISMA (Preferred Reporting Items for Systematic Review and Meta-analysis) method, which is carried out systematically. The research was conducted in December-February with a review of articles published in the last 5 years (2018-2023). Researchers searched for literature independently through PubMed and Science Direct.Results:Triple drug therapy or a combination of Ivermectin-Diethylcarbamazine -Albendazole (IDA) is safer and more tolerable for filariasis than dual drug (combination of Diethylcarbamazine -Albendazole/DA), according to various articles. In addition, IDA reduces microfilaria formation more than DA. Most filariasis treatment side effects are modest, such as fever and soreness.Conclusion: In comparison to dual drug therapy, triple drug therapy exhibits a substantial advantage; however, the level of endemicity and the species of the causative agents must be considered when applying this approach.